Social Justice, Artistic Practice and New Technologies: Gender and Disability Activisms and Identities in Film and Digital Video - Hladki, Janice (Atlantis, 2008)
Contemporary disability cultural production is under-researched in feminist and cultural theory. Focusing on the film and digital video trilogy, Whole: A Trinity of Being, by South African visual poet Shelley Barry, this paper examines how her work theorizes disability and gender and critically interrogates possibilities for social justice.